Rekrutmen BUMN : Antara Transparansi dan Titipan Jabatan - Fadilla Putri Awalia; Ikwan Arwan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This research study examines the dynamics of organizational communication and public communication in the recruitment process in State-Owned Enterprises (SOEs), with a particular focus on the tension between transparency efforts and the ongoing practice of entrusting positions. Despite the government's introduction of the Joint Recruitment of SOEs (RBB) program, which aims to digitize and standardize the selection of employees, a discrepancy emerges between the program's stated objectives and the perceptions of both the government and the public. The prevalence of complaints pertaining to the absence of information transparency, the lack of feedback mechanisms regarding unsuccessful outcomes, and the emergence of the term "insider" within the digital domain are indicative of deficiencies in two-way communication and a decline in public trust in the BUMN recruitment process. The present research employs a descriptive qualitative approach, utilizing a case study method and thematic analysis. The data presented herein were obtained through meticulous documentation studies of official documents from the FHCI, the Ministry of SOEs, and online media, as well as netnographic observations of public interactions on social media such as Instagram and Twitter. The analysis focused on public narratives, institutional communication patterns, and their impact on institutional reputation and legitimacy. The findings indicate that organizational communication within the RBB process remains hierarchical, failing to align with the ideal of reciprocal communication. The absence of information disclosure and the lack of a designated public forum for clarification engender significant discord between the assertions of institutional entities and the actual experiences of participants. This research recommends the implementation of measures to enhance the effectiveness of the aforementioned processes.